Propylene column pressure relief valves chattering resulting in explosion and fire of the Steam Cracker unit. (January 2022) - Herink, Tomas; Doskočil, Jan; Růžička, Martin; Henry, Philp A.; Sadowski, Robert A.; Zámostný, Petr
Abstract: The Refinery and petrochemical production facilities process and produce the gaseous and liquid flammable hydrocarbons under the pressure conditions. In case of any failure, improper design or human mistake there can be autonomous and independent pressure relieve systems activated to release the pressure to the flare systems to protect the equipment against the overpressure, damages and other consequences. The paper describes the failure occurred at the Steam Cracker unit in Litvinov, Czech Republic in 2015. As a result of a loss of cooling followed by loss of reflux event, the pressure relief system of the Propylene Column was activated whereas the pressure relief valves opened up and chattered, resulting in loosening of flange bolts and loss of containment. The release of the propylene vapor ignited, resulting in subsequent explosion and fire at the Propylene Column area. The interruption of steam and instrument air supply caused by the fire damages led to the other extensive fire of four pyrolysis heaters. The extraordinary event description, root cause analysis, investigation as well as the corrective actions are introduced and analyzed. Highlights: The pressure relief system must be the autonomous and independent protection of chemical production facilities. The proper design of the pressure relief system must be done following strictly defined rules. The pressure relief valves chattering can be the root cause of the loss of containment. The obsolete design of the pressure relief system can lead in to the serious incident such as explosion and fire.